Synthesis of silver leaves and their potential application for analysis and degradation of phenolic pollutants - Jianan Sun; Xianhui Gao; Wei Wei (IET Nanobiotechnology)
Abstract A one‐pot bottom‐up synthesis method was used to synthesise multi‐level leaf‐like nano‐silver (silver leaf) by simply mixing AgNO3, L‐ascorbic acid, Sodium sodium citrate, and polyvinylpyrrolidone (PVP) in the ethanol‐water mixed solvents. Scanning electron microscopy (SEM) characterisations show that the silver leaves have tertiary structures and their sizes are controllable. In addition, silver leaves exhibit excellent Raman enhancement effect (SERS) and chemical catalytic activities for phenolic molecules. Interestingly, the SERS and catalytic activities increase as the size of the silver leaves decrease within a certain range, but when the size is too small, both of these performances weaken. The nanometre size and interstitial structure have a common amplification effect and influence on these activities. The present work not only showed a new method for the synthesis of silver leaves but also could be generalised to find other metallic leaves that could be used as promising heterogeneous catalysts for various reactions. The production of such small‐sized silver leaves will facilitate the analysis of phenolic pollutants through Raman enhancement and treat these pollutants through catalytic degradation.